Efisiensi Biaya Pakan Melalui Pemanfaatan Rayap Pohon (Coptotermes sp.) dalam Pembesaran Ikan Mas Komet(Carassius auratus auratus) - Ida Lapadi; Farida Wouw; Nurhani Widiastuti (Jurnal Sumberdaya Akuatik Indopasifik, 2017)
The purpose of this research are to know comet goldfish growth by percentage termites and pelet feed, Food Convertion Ratio (FCR) and Food Efficiency (FE) of each treatment, and analyze the cost of feed consumed. The treatment on this study using termites feed and pelet by different percentages. Aquarium A treatment = 20% termites; 80% pelets, aquarium B = 40% termites; pelets 60% and aquariums C = termites 60%; pelet 40%. The results showed that the percentage of pellet feed on termites and provide a better relative growth in treatment A 0.42 grams, C 0.26 grams and 0.10 grams B. FCR best value is obtained by treatment A 2.04 followed by C 3.3 and B 7.9. Similarly, the value of feed efficiency best values ​​obtained by the treatment of A 51.6%, followed by C 29.58% and B 11.02%. Values ​​lowest feed costs obtained by the treatment A Rp. 4112, -, followed by C Rp. 4496, - and B Rp. 5008, -. Results showed that utilization of 20% termite can be a complementary feed in comet fish rearing.